Theory, Practice, and Nature In-between: Antonio Vallisneri's 'Primi Itineris Specimen' - Luzzini, Francesco (Sources 9: Max Planck Research Library for the History and Development of Knowledge, 2018)
In the summer of 1704, Antonio Vallisneri (1661-1730), the preeminent Italian physician and natural philosopher of his time, traveled with a "daring soul" and "trembling feet" across the "silent horrors" of the northern Apennines: down the hills south of Reggio Emilia to northern Tuscany and the western edge of his native land, the Province of Garfagnana. He then wrote a report of this adventure, the Primi Itineris per Montes Specimen Physico-Medicum ("Physico-medical example of a first journey through the mountains"), and sent it to the Royal Society of London, hoping for its publication in Philosophical Transactions. Unfortunately this did not happen and the manuscript disappeared from sight. The original draft, however, survived in the State Archive of the Italian city of Reggio Emilia where it was found in 2009. With its exceptional array of geological, medical, geographical, technical, ethnographic, and historical data, the Primi Itineris Specimen is one of the earliest and most well-documented attempts to define a systematic approach to field research. Its frantically reworked pages and anxious marginal notes offer a new and precious opportunity to understand why and how experimental data and theories in the early modern period interacted and shaped the development of many crucial debates. These include the discovering of deep-time, the comprehension of geological phenomena (such as the hydrologic cycle and the origin of mountains and fossils), the perception of man's place in nature, the constant search for new therapeutics, the tormented and charming relation between science and religion.